2022
DOI: 10.35516/jjps.v15i3.411
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes and Practice toward Antibiotic Use among Under and Post-Graduate Students at Yarmouk University in Jordan: A Descriptive Study

Abstract: Objective: Irrational and overzealous use of antibiotics in addition to multidrug resistance has increased at an alarming limits around the world.  This study aimed to evaluate the knowledge and practices toward antibiotic use among students at Yarmouk University Material and Method: A cross-sectional descriptive survey using a structured electronic version of valid questionnaire was distributed among participants. Google form was prepared based on available questionnaire in literature, revised by a grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…It was reported that undergraduate pharmacy students from Zambia, despite demonstrating acceptable knowledge and attitudes towards antimicrobial use and resistance, still warranted an improvement in practice [ 29 ]. Two studies from Jordan assessed the knowledge, attitude and behavior of medical and nonmedical students as they related to antibiotic use and resistance; however, details regarding enrollment were not included [ 30 , 31 ] Pharmacy students in Jordan were surveyed and reported adequate knowledge, attitude and practice toward antibiotic use [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that undergraduate pharmacy students from Zambia, despite demonstrating acceptable knowledge and attitudes towards antimicrobial use and resistance, still warranted an improvement in practice [ 29 ]. Two studies from Jordan assessed the knowledge, attitude and behavior of medical and nonmedical students as they related to antibiotic use and resistance; however, details regarding enrollment were not included [ 30 , 31 ] Pharmacy students in Jordan were surveyed and reported adequate knowledge, attitude and practice toward antibiotic use [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…As part of further assessing participants' understanding of antibiotic indications, and the impact of their inappropriate use on both immunity and resistance, we found that 67.9% (n=362) of the participants believe antibiotics can cure all infections. Also, 70.4% (n=375) consider using them for bone and body pain, a finding that is also common among university students in Jordan [28].…”
Section: Discussionmentioning
confidence: 99%
“…However, significant percent of the respondents reported high-risk practices such as using ethanol, hypochlorite, and diluted chloroxylenol to wash fruits and vegetables, -91 -mixing disinfectants, diluting disinfectants with hot water, and applying disinfectants and cleaning products to bare skin. Nonetheless, such poor practices may yield hazardous effects, such as tissue damage and injuries [32][33][34][35] .…”
Section: Discussionmentioning
confidence: 99%